Republic of Palau : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The report discusses the needed fiscal adjustment under the no Compact renewal and Compact renewal scenarios, respectively. The report also discusses the IMF estimates and projections of the Republic of Palau's selected social indicators, 1995 and 2000-07; gross domestic product during 2002-07; national government debt and debt service, 1999/00-2006/07; national government budgetary operations, 2001/02-2007/08; national government expenditure, 2001/02-2006/07; details of assets and liabilities; operating accounts of the national development bank of palau; financial positions of the civil service pension fund, 2000/01; 2006/07, et cetera.